PARAMETER KUALITAS AIR PADA TAMBAK PEMBESARAN UDANG VANNAMEI (Litopenaeus vannamei) DI CV. SUKSES INDAH PRIMA, SITUBONDO, JAWA TIMUR - jayanti, shara; Maharani, Chafsoh Attyra; Anna, Fauziah; M. E, Fauzi (MARLIN, 2024)
This study aims to determine the effect of air quality dynamics in ponds owned by CV. Sukse Indah Prima Situbondo, East Java on ADG and ABW and shrimp mortality. The air quality results for the C2 plot during the checking were optimal, that is, they met the standard, even though the results were different from the 2014 laboratory/SNI standards. The results of the checking on the C6 plot contained several optimal checking results. However, there are still a number of checks that exceed the standard and experience a drastic increase or decrease, such as ammonium and alkalinity, as well as TVC whose brightness fluctuates drastically. The survival of the C2 plot was 95%, the C6 plot was 60%, the mortality in the C2 plot was 5%, and the C6 plot was 40%, and the ABW results experienced an increase in weight and length for each sampling. As a comparison, ADG decreased in the C2 DOC 54 plot, while the C6 plot experienced an optimal increase.